PENETAPAN TARGET TERHADAP STICKINESS COST - Windyastuti Windyastuti (Jurnal Keuangan dan Perbankan, 2013)
This study aimed to analyze the influence of manager targeting to the stickiness cost. The research data was amanufacturing companys financial statements during 1999-2011 published at BEI. The research data includedcost of sales, administration and general, net sales and Price Earnings Ratio (PER). This study used adynamic panel data regression analysis. The results showed that cost of sales, administration and general weresticky. Furthermore, manager targeting caused the stickiness degree of sales, administration and general costlower. Manager targeting changed the managers behavior. When the net sales declined, manager reduced theresource use drastically so the cost of sales, administration and general also decreased drastically.